An Assessment of Old and New Characters Using Traditional and Geometric Morphometrics for the Identification of Dendroctonus approximatus and Dendroctonus parallelocollis (Curculionidae: Scolytinae). Issue 1 (2nd February 2019) - García-Román, Jazmín; Armendáriz-Toledano, F; Valerio-Mendoza, O; Zúñiga, Gerardo
Abstract: There have been numerous changes in the nomenclature of species of Dendroctonus . The case of Dendroctonus parallelocollis Chapuis and Dendroctonus approximatus Dietz has been particularly noteworthy. These bark beetles colonize pine trees but are not aggressive species. The high morphological similarity, their overlapping geographical distribution, and the limited knowledge of these species have resulted in taxonomic confusion. The aim of the present study was to assess morphological characters reported in the literature and to scrutinize new characters that might be useful for the separation of these species. We evaluated 26 morphological attributes and performed geometric morphometrics analysis of the antenna, pronotum, spermatheca, and seminal rod to test if the variations in the shape of these structures allow the recognition of additional discrete characters to differentiate them. Our results show that five double-state characters of external morphology are useful to identify these species, and the shape of antenna, spermatheca, and seminal rod.